Impaired V(D)J Recombination and Lymphocyte Development in Core RAG1-expressing Mice - Dudley, Darryll D. (The Rockefeller University Press, 2003)
RAG1 and RAG2 are the lymphocyte-specific components of the V(D)J recombinase. In vitro analyses of RAG function have relied on soluble, highly truncated “core” RAG proteins. To identify potential functions for noncore regions and assess functionality of core RAG1 in vivo, we generated core RAG1 knockin (RAG1(c/c)) mice. Significant B and T cell numbers are generated in RAG1(c/c) mice, showing that core RAG1, despite missing ∼40% of the RAG1 sequence, retains significant in vivo function. However, lymphocyte development and the overall level of V(D)J recombination are impaired at the progenitor stage in RAG1(c/c) mice. Correspondingly, there are reduced numbers of peripheral RAG1(c/c) B and T lymphocytes. Whereas normal B lymphocytes undergo rearrangement of both J(H) loci, substantial levels of germline J(H) loci persist in mature B cells of RAG1(c/c) mice, demonstrating that DJ(H) rearrangement on both IgH alleles is not required for developmental progression to the stage of V(H) to DJ(H) recombination. Whereas V(H) to DJ(H) rearrangements occur, albeit at reduced levels, on the nonselected alleles of RAG1(c/c) B cells that have undergone D to J(H) rearrangements, we do not detect V(H) to D(H) rearrangements in RAG1(c/c) B cells that retain germline J(H) alleles. We discuss the potential implications of these findings for noncore RAG1 functions and for the ordered assembly of V(H), D(H), and J(H) segments.